PEMANFAATAN LIMBAH BANGKAI AYAM BROILER UNTUK PEMBUATAN PAKAN LELE - Supartini Supartini; Ririk Yunita Hendry Koesworo Sari; Wahyu Widarjo (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
This article presents the results of IbM’s activities which related to an effort to overcome theproblem of environment pollution, the problem of waste chicken, and the problem ofunemployment in Desa Bandardawung Tawangmangu Sub-Distric Karanganyar Distric.Thefirst aims of this activities is to decreasing the environment pollution problems whichcaused by waste chicken ( dead chicken) from the chicken slaughterd houses. The secondaims is to produce dan to use the waste chicken. Futhermore, the third aims is to open newbusiness field in the form of catfish farming for the unproductive member of Karang TarunaRW 07 and RW 08 Desa Bandardawung, by recycling waste as catfish food. The specialtarget expected from this program is to empower the member of Karang Taruna and takeadvantage of chicken carcass waste. The method are used to reach this aims are bycoaching, training and mentoring activities. Evaluation of chicken carcass waste handling,training and counseling, monitoring, and mentoring. This program had been transferredsuccessfully to the members of karang taruna as expected.Keywords: Chicken carcass waste, catfish food, catfish farming